Inflammation in Murine Aneurysm Healing: The Role of CXCL1. (1st September 2019) - Patel, Devan; Motwani, Kartik; Hosaka, Koji; Hoh, Brian L
Abstract: INTRODUCTION: Cerebral aneurysm rupture results in subarachnoid hemorrhage which has a mortality of up to 40%. Current prophylactic treatment options include surgical clipping, flow diversion, and endovascular coiling. A significant drawback of coiling is that up to 20% of aneurysms recur and require retreatment due to insufficient fibrotic healing. Thus, it is crucial to develop more effective treatments. As inflammation appears to be critical in cerebral aneurysm pathophysiology, it is necessary to investigate aneurysm healing in the context of key inflammatory mediators. Using a novel in Vitro flow chamber model, we found increased expression of CXCL1, a neutrophil chemoattractant, at arterial bifurcations and in aneurysms. We hypothesized that CXCL1 is a key mediator in aneurysm healing. METHODS: Using our murine aneurysm healing model, aneurysms were created in the right common carotid artery of female C57BL/6 mice using elastase. Three weeks later, aneurysms were implanted with either poly (lactic-co-glycolic acid) (PLGA) + CXCL1—coated coils or PLGA only—coated coils. Three weeks after coil implantation, aneurysms were harvested for data collection. In a subsequent experiment, the same aneurysm model was used but all mice were coiled with PLGA-coated coils. Animals were randomly assigned to receive intraperitoneal injections of either CXCL1 neutralizing antibody or IgG control. Three weeks after coiling, aneurysms were harvested for data collection. RESULTS: Animals treated with PLGA + CXCL1—coated coils had significantly decreased aneurysm healing than those treated with PLGA only—coated coils (21.8% vs 39.8%, P = .048). Animals treated with CXCL1 neutralizing antibody had significantly increased aneurysm healing compared to IgG control (63.8% vs 42.4%, P = .00012). CXCL1 neutralizing antibody also decreased neutrophil infiltration into the aneurysm compared to IgG control (2.0 cells/hpf vs 5.4 cells/hpf, P = .03). CONCLUSION: Our findings suggest CXCL1 decreases murine aneurysm healing after coil implantation. Therapeutic intervention with CXCL1 neutralizing antibody appears to increase aneurysm healing by decreasing neutrophil infiltration.